FILSAFAT PERENIALISME SEBAGAI LANDASAN PENDIDIKAN KARAKTER ISLAMI - Ba'ina, Sitti; Hadzafi, Mohon. Iqbal (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This research was conducted to analyze the philosophy of perennialism as the foundation of character education. Character education is very necessary in learning because nowadays there is a rampant multi-dimensional crisis, ranging from social deviance and uncommendable behavior which is caused by the development of the times that have begun to be exposed to western culture and are not in accordance with the existing culture in Indonesia. This study uses a qualitative method with a literature study approach. The results of the study show that the view of Islamic education towards the philosophy of perennialism is grouped into five: first, Perennialism in the context of education is built on the basis of one ontological belief, second, for the school of Perennialism education is the transfer of knowledge about eternal truths, third, Perennialism is more inclined to the subject-oriented aspect, in the curriculum as well as in the methods and approaches taken in the learning process, fourth, Perennialism is more inclined to the subject oriented aspect, in the curriculum and in methods, fifth, the power of reason/discourse, knowledge of spiritual experience (Sufi/mysticism).